How Does Islamic Education Integrate Islamic Values into The Modern Curriculum? - Fifa Chorina Azka Qonita; Nasywa Yumna; Luthfitarizha Balen Azahra; Marwa Putri Sholekah (Universitas Muhammadiyah Surakarta, 2025)
This study explores how Islamic education integrates Islamic values into the modern curriculum. The research examines the challenges of blending traditional Islamic teachings with contemporary educational demands. Employing qualitative methods, the study highlights the strategies educators use to align Islamic principles with modern academic requirements, including thematic integration, character building, and technology adaptation. Results indicate that incorporating Islamic values enhances students’ moral development and academic performance. Future recommendations include designing teacher training programs and innovative curriculum frameworks that bridge the gap between faith and contemporary learning.